Association Between Inflammatory Potential of the Diet and Ulcerative Colitis: A Case-Control Study - Khademi, Zeinab; Saneei, Parvane; Hassanzadeh-Keshteli, Ammar; Daghaghzadeh, Hamed; Tavakkoli, Hamid; Adibi, Peyman; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2021)
Background/Aim: Despite the inflammatory potential of inflammatory bowel disease (IBD), limited data are available on the association of inflammatory potential of the diet and risk of ulcerative colitis (UC). We aimed to investigate the association of inflammatory potential of the diet (IPD) and odds of UC risk in a case-control study. Methods: Patients with UC were enrolled from Iranian IBD registry, whose disease was confirmed by a gastroenterologist. Controls were selected randomly from SEPAHAN study (Studying the epidemiology of psycho-alimentary health and nutrition), a large population-based study on more than 8000 apparently healthy individuals. Dietary intakes of 28 food items obtained from a validated dish-based food frequency questionnaire (FFQ), was used to computed IPD. Results: This case-control study was carried out among 109 cases and 218 randomly chosen controls. Mean age of cases and controls was 39.5±10.0 and 41.5±11.8 y, respectively. Totally, 67% of study participants were female and 33% were male. After controlling for age, sex, and body mass index (BMI), we found that the patients with UC were more likely to be in the highest quartile of IPD compared with controls (OR: 2.83; 95% CI: 1.41-5.69, P-trend<0.001). This association strengthened after additional adjustment for education, cigarette smoking, medical history, and physical activity (OR: 3.48; 95% CI: 1.32-9.1, P-trend=0.003). When we took dietary habits into account, the association was slightly attenuated (OR: 3.33; 95% CI: 1.20-9.20, P-trend=0.005).